Disasters, economic growth and fiscal response in the countries of Latin America and the Caribbean, 1972-2010: Omar D. Bello - Omar D. Bello (CEPAL Review, 2017)
The aim of this study is to estimate the impact of geological and climate-related disasters on the per capita growth rates of gross domestic product (GDP) and fiscal expenditure in Latin American and Caribbean countries. The results show that the effects vary by type of disaster and by subregion. In the Caribbean countries, the per capita GDP growth rate has typically responded negatively to climate disasters, whereas the response to a geological disaster has generally not been statistically significant. In Central American countries, the response of the per capita GDP growth rate was found to be negative in the first year and positive in the third year in the case of climate disasters, but positive in the second and third years for disasters of geological origin.